«Կարմիր Քրդստան». պատմա–քաղաքագիտական ակնարկ - Բաբայան, Դավիթ (Ասողիկ հրատ.)
On July 23, 1923 the territories of later to be know as Kelbajar, Lachin and Kubatly regions were united to form a separate Kurdistan uyezd (area), which is more known as Red Kurdistan. Interestingly, but infoimation about the formation of a Kurdish administrative unit was disseminated back in 1921. For example, on October 3, 1921 Russian Federation People's Commissariat on Nationalities headed by Joseph Stalin in its newspaper published an article where it informed Soviet public that the formation of а Kurdish Republic was in process.
Keywords: Պատմություն; Քաղաքագիտություն